Estudo das alterações vasculares em um modelo de obesidade induzido por dieta palatável: papel da leptina - Josiane Fernandes da Silva (2011)
Obesity results from the interaction among several genetic and environmental factors, and is frequently associated with metabolic disorders and vascular changes. Currently, adipose tissue is known as an endocrine organ, due to the production of several biologically active substances, such as adipokines and cytokines. Synthesis of vasoactive adipokines may be the base of changes in vascular function regarding obesity. Leptin is an adipokine which, among other things, influences the cardiovascular system. It is able to modulate the vascular tonus, increasing the expression and activity of eNOS (endothelial nitric oxide synthase) in some vascular beds. The purpose of this study was to investigate vascular changes in a model of obesity induced by a palatable diet and the role of leptin in these changes. Rats (4 weeks of age) fed with the diet (D) (to 5 weeks) compared with control animals (C) presented a greater body weight gain (C= 193.4 ± 9.6; D=247.5 ± 10.5 g; p<0.001) and retroperitoneal (C=0.9 ± 0.1; D=1.9 ± 0.13 g/100g; p<0,0001) and epididymal fat accumulations (C=0.82 ± 0.06; D=1.56 ± 0.10 g/100g p <0,0001). These results have shown that a diet enriched with condensed milk was able to induce obesity in the treated animals. These data are supported by the calculus of alimentary effectiveness and Lee index, which were significantly higher in obese animals, suggesting that the diet favored nutrient stock. Obese animals have shown a better vasorelaxant response to acetylcholine (ACh) (p<0.05). In addition, they presented a lower contractile response to phenylephrine (p<0.001). This hyporeactivity was reverted by removing the endothelium and by non-selectively inhibiting nitric oxide synthase (NOS) with L-NAME (300 M), and by selectively inhibiting eNOS with L-NNA (1 M), but was not changed by inhibiting inducible nitric oxide synthase (iNOS) with 1400w (5M). Basal nitric oxide (NO) production and stimulated by acetylcholine was significantly larger in obese animals (p<0.05). Western blot experiments have shown increased levels of eNOS expression, but not iNOS. Plasma concentrations of leptin were increased in obese animals (C=1.15 ± 0.02; D=1.99 ± 0.23 ng/ml p<0.01). Aortic rings from control animals, pre-incubated with leptin 1M for six hours, have shown a reduced contraction in response to phenylephrine (p<0.01) and a higher vasodilator response to ACh (p<0.05), similar to obese animals. Leptin has also induced an increased NO production which was abolished by eNOS inhibition with L-NNA (1 M). Taken together, our data suggest that there is a vascular change in obese animals characterized, mainly, by a reduction in the contractile response. This reduction in IX contractile response is probably a consequence of a larger NO production, due to an increase in the eNOS expression, stimulated by the increased leptin levels in obese animals, because treatment with leptin mimicked the effects of diet